CYSTIC FIBROSIS: DIAGNOSIS, TREATMENT AND THERAPEUTIC UPDATES - Lopes, Leticia Gabriele Pereira; dos Reis, Maria Luiza Martins; de Faria, Heloisa Benfica; Araújo, Lanna Gonçalves; Carvalho, Daisy Laurinda Santos Pina; Santana, Ianca Gontijo Cavalcante; Lago, Heloiza Dias Lopes; Silva, Pedro Henrique de Almeida (CIPEEX, 2025)
Introduction: Cystic fibrosis (CF) is a genetic disease characterized by mutations in the CFTR gene, which primarily affect the respiratory and digestive systems, resulting in impaired lung function, malnutrition, and reduced quality of life. Early diagnosis is crucial for implementing effective therapeutic interventions, allowing for the prevention or minimization of respiratory and nutritional complications. Recent advances in treatment, particularly CFTR modulators, have demonstrated significant impact on improving lung function, controlling respiratory exacerbations, and improving quality of life, representing a paradigm shift in the management of CF. At the same time, traditional therapies, such as respiratory physiotherapy, antibiotics for infection control, nutritional support, and multidisciplinary follow-up, remain essential for reducing complications and maintaining the overall health of patients. Objective: To review the literature on diagnosis, clinical management, and therapeutic advances in patients with cystic fibrosis. Methods: This study consists of a literature review based on the PICO strategy, including articles published in the last five years, in English or Portuguese, that address the diagnosis, management, and therapies of CF. Searches were conducted in PubMed, SciELO, and BVS databases, using the descriptors "cystic fibrosis" AND diagnosis AND treatment AND therapies. Results: The results show that integrating early diagnosis with innovative and conventional therapies provides better clinical outcomes, prolonging survival and promoting a better quality of life. Conclusion: A combined approach, combining CFTR modulators with traditional care, is the most effective strategy for managing cystic fibrosis, reinforcing the importance of continuous multidisciplinary monitoring.